Screening and Selection of Native Lactic Acid Bacteria Isolated from Chilean Grapes - Carla Vargas-Luna; Liliana Godoy; Sergio Benavides; Consuelo Ceppi de Lecco; Alejandra Urtubia; Wendy Franco (Foods)
The aim of this study was investigating the biological diversity of lactic acid bacteria isolated from Chilean grapes and identifying potential candidates for use as malolactic fermentation starter cultures. The isolated bacteria underwent a comprehensive six-stage screening process, which was mutually exclusive except for the evaluation of tyramine production and citric acid intake. This process included morphological, metabolic, fermentation yield, and resistance tests to identify promising malolactic strains. Morphological assessments led to the selection of 23 isolates, which were genetically identified as Levilactobacillus brevis (65% abundance) and Leuconostoc mesenteroides (35% abundance). Among these, eight strains exhibited low sugar metabolism rates, while three demonstrated competitive growth and malolactic activity in a synthetic medium containing 10% ethanol, outperforming a commercial strain. Low consumption was observed in the qualitative citric acid intake test, whereas a positive response was noted for tyramine production. At the conclusion of the sequential selection criteria, Levilactobacillus brevis BCV-46 exhibited the most favorable characteristics for potential use as a malolactic starter culture, successfully withstanding the combined stress factors of ethanol, pH, and SO2.